Health policy, power and politics : sociological insights - Calnan, Michael (Emerald Publishing Limited, 2020)
In the context of substantial changes in health service policy and public health policy in England over the last two decades, Health Policy, Power and Politics fills an important gap by providing an up-to-date and accessible account of recent trends in health policies and a sociological analysis of why these policies have taken the shape they have. This book provides a theoretically informed analysis of key recent policy changes in England and how the interplay of powerful structural interests has influenced policy in health. It includes chapters on recent reforms in the NHS and the drift towards privatisation, policies aimed at enhancing public and patient involvement, the regulation of the drug industry, medicalisation and mental health policy, the role and effect of the media and recent changes in social and environmental health policy. The analysis examines the influence of the State, professional medicine, the media, commercial interests such as those of the pharmaceutical, food and fossil fuel industries, patient's groups and the wider global environment. While the key focus of the book is on England, the analysis drawn on by the author comes from a plethora of policy examples in health systems in high and low to middle income countries across the world. This widened context shines a light on the influence of globalisation and highlights both the distinctive character of health policy in England, as well as the common themes it shares in a world-wide context.